Perceptions, stereotypes and cognitive resources of female businesspersons: A social identity approach - LIM, Amy J. Y. (Institutional Knowledge at Singapore Management University, 2015)
According to the Stereotype Content Model (SCM), female businesspersons are often stereotyped and labeled either as a Career Women, competent but cold, or as a Traditional Women, warm but incompetent. This suggests that female businesspersons are generally perceived to be either competent or warm individuals, but not both. However, this may not reflect female businesspersons’ own perceptions of their competence and warmth in the workplace. Contrary to the stereotypes, evidence has demonstrated that some female businesspersons display behaviors that signal both competence and warmth. Employing a social identity approach, I propose that gender-professional identity integration (G-PII), an individual difference that refers to the perceived compatibility between the female identity and professional identity, plays a crucial role in how female businesspersons perceive themselves and manage the stereotypes they face in the workplace. Study 1 found that female business students do not differ in their perceived co-existence of competence and warmth of themselves. However, they differed on the perceptions they had of another female professional depending on their level of conflict between their dual social identities. Female business students with lower levels of conflict were also found to endorse female businesspersons stereotypes less. Study 2 revealed that female business students with higher levels of conflict were more ego-depleted when asked to integrate identity-related knowledge systems simultaneously, suggesting lesser availability of self-regulatory resources to cope with stereotypes. Theoretical and practical implications of the findings are discussed.